E-mail-based health care in patients with dementia during the pandemic - Altunkalem Seydi, Kubra; Ates Bulut, Esra; Yavuz, Idil; Kavak, Hemrin; Kaya, Derya; Isik, Ahmet Turan (Frontiers in Psychiatry, 2022)
Introduction/aim Frail and cognitively impaired older patients are particularly vulnerable groups during the pandemic. Lockdowns, social isolation, and physical inactivity considerably affect physical and mental wellbeing. During the pandemic process, routine medical checks and acute medical care services may be disrupted. The study aimed to demonstrate the feasibility and effectiveness of telemedicine in the delivery of healthcare services to elderly patients during the pandemic. Materials and methods E-mails sent to the e-mail address of the department of geriatrics, which has been actively used for 4 years, between April 2020 and June 2021, were retrospectively evaluated. The time and reason for each application, referral to the patients, demographic data of the patients, and chronic diseases were recorded. E-mail frequencies were considered monthly time series, and time series charts for e-mail frequencies from patients were produced. Results A total of 374 e-mails that 213 patients sent were assessed. A vast majority, 97.6% of the e-mails, were sent by proxies. The mean age of patients was 78.7 ± 8.1 years, and 59.2% were women. Hypertension and dementia were the most common comorbidities. The applications mostly occurred in April-May and October-November 2020. The most common complaint in dementia was behavioral disturbances (13.6%). Geriatric outpatient appointments were arranged for 29.9% of the applicants, 14.2% were referred to the emergency department, and 23.0% were offered medical treatment. Outpatient examination and treatment were completed in 15% of the patients and 10.4% of them were hospitalized. The time series charts showed that e-mails were sent more frequently by patients with dementia than the others (p = 0.03). Conclusions Telemedicine, which enables many problems of patients to be solved in geriatric practice without face-to-face appointments, can also prevent infections and unnecessary hospitalizations, especially during these unusual pandemic days.